2018
DOI: 10.1061/(asce)me.1943-5479.0000606
|View full text |Cite
|
Sign up to set email alerts
|

Finding Differences among Construction Companies’ Management Practices and Their Relation to Project Performance

Abstract: 6The performance of construction companies is linked to the performance of their projects, as 7 their financial success as well as the satisfaction of their clients depends on it. However, most 8 studies of construction companies' performance consider mainly the corporate aspects but not 9 the performance they achieve in their projects that are a result of their management practices. 10A key issue is determining the differences among management practices used by construction 11 companies that provide them with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
0
18
0
8
Order By: Relevance
“…Although it is an important part of the organization's management (Pellicer et al, 2017), innovation has the disadvantages that its processes are not completely understood (Lindgren et al, 2018), it is considered unnecessary in the short term (Castillo et al, 2018), and it does not have specific departments for its standardized management, all of which affect the potential benefits (Hadiwattege et al, 2018). On the other hand, it represents uncertainty (Kildienė et al, 2014) when it is adopted, although this can be mitigated through standardization (Yepes et al, 2016).…”
Section: Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is an important part of the organization's management (Pellicer et al, 2017), innovation has the disadvantages that its processes are not completely understood (Lindgren et al, 2018), it is considered unnecessary in the short term (Castillo et al, 2018), and it does not have specific departments for its standardized management, all of which affect the potential benefits (Hadiwattege et al, 2018). On the other hand, it represents uncertainty (Kildienė et al, 2014) when it is adopted, although this can be mitigated through standardization (Yepes et al, 2016).…”
Section: Innovationmentioning
confidence: 99%
“…Knowledge is a product of learning (Qian Li et al, 2017) that allows employees to act and make better decisions, becoming in the long term an added value. It has always been considered an abstract concept, associated with intangible assets (Hartono et al, 2019), a main challenge being the management of knowledge assets (Hoła et al, 2015), which is the core of knowledge management (Castillo et al, 2018). The more knowledge remains tacit, the more difficult its management is (Zhang & He, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ho (2016) proposed that construction contractors should adopt a low-cost strategy when construction market rivalry is strong and clients are powerful and use a differentiation strategy when there is high substitution for their services. Castillo et al (2018) suggested using lean production and communicating company policies to new personnel to manage the cost and improve the firm’s financial performance. Risks such as political, economic, social, employer and contractual should be assessed and managed before submitting a bid because these affect the project cost and contractors’ financial performance (Jung and Han, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Construction management practices have been identified as causes and also suggested as solutions at project and/or organization level. There is a relationship between management practices and performance in construction industry (Castillo et al , 2018). Construction management practice areas are interrelated; for example, cost management practice is related with planning and scheduling; similarly, it is related to quality management, and these all are affected by organization culture.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Different classifications have been given for construction management practices. Castillo et al (2018) built on the work of Ramirez et al (2004) and listed 15 management dimensions to study construction companies’ management practices: quality, communication and information, costs and schedule, leadership, corporate goals, organizational change, planning and programming, production, human resources, relations with owner, health and safety, technology, supply, risk and innovation. These studies focus on construction companies’ management practices.…”
Section: Literature Reviewmentioning
confidence: 99%